Analisis Efektitas Kebijakan Publik Dalam Upaya Perberdayaan Masyarakat, di Kecamatan Kintamani, Kabupaten Bangli. - Drs. I Wayan Sedia, M.I.Kom Sedia (UHN IGB Sugriwa Denpasar, 2022)
In order to reduce poverty in Kintamani, this research intends to identifythe primary barriers to community empowerment, the efforts made bylocal governments, and the local wisdom of putting indigenousknowledge—such as the principles found in Tat Twam Asi—to use. Inorder to ascertain if governmental policies in the Kintamani Sub-District,Bangli District, were effective in promoting community empowerment,this study employed interview and observational methods. The datagathered was then evaluated and presented descriptively. According tothe study's findings, attempts to empower and reduce poverty inKintamani were significantly affected by Bangli local government policies,culture, and local wisdom. The primary issues impeding attempts toeliminate poverty in Kintamani are regional policies that areinappropriate and in contradiction with local needs and customs. Besides,the traditions of society are difficult to change following thedevelopments and dynamics of the times.